THE IMPLEMENTATION OF INQUIRY-BASED LEARNING IN TEACHING WRITING NEWS ITEM TEXT - Rika Tresnawati (Journal of English Education Program (JEEP), 2021)
This study was aimed at finding out teacher’s way in teaching writing news item through Inquiry-Based Learning, its problems encountered by the teacher, and teacher’s ways in overcoming it. A qualitative approach with the type of case study was utilized to collect the primary data involving an English teacher who taught news item text through IBL. Classroom observation and interview were the instruments in this research which were analyzed qualitatively. Based on the research findings, the writer found that the teacher used the steps in implementing IBL as suggested by Lee et al., (2004, p. 23) including planning, creating, processing, sharing and retrieving, and evaluating. The writer also found that the teacher encountered difficulties in guiding the students to find out the information in order to fulfill teacher’s instructions by some questions generated in the white board. To solve that problem, the teacher encouraged the students to communicate intensively in their group. The findings suggest that IBL, as one of the approaches to teaching English, should be applied by the teachers in various ways with the reference to the steps in implementing IBL. Keywords: IBL, news item text, teaching writing